Research Progress on the Correlation Between Gardnerella Typing and Bacterial Vaginosis - Qin, Hanyu; Xiao, Bingbing (Frontiers in Cellular and Infection Microbiology, 2022)
Bacterial vaginosis (BV) is the most common infectious disease of the reproductive tract in women of childbearing age. It often manifests as an imbalance in the vaginal microbiome, including a decrease in Lactobacillus and an increase in anaerobic bacteria. While Gardnerella spp. are considered a major cause of BV, they are also detected in the vaginal microbiome of healthy women. G. vaginalis was the only recognized species of Gardnerella until a recent study characterized three new species, G. leopoldii, G. piotii, and G. swidsinskii. This review describes the different types and genetic diversity of Gardnerella, as well as new findings on the correlation between different Gardnerella spp. and BV.